Influência de fatores maternos no acometimento da cárie na primeira infância: um estudo piloto - Priesnitz, Thaynara Fernanda (2020)
Early childhood caries (ECC) is defined by the presence any type of carious lesion in children under the age of six. It is a biopsychosocial condition caused by the imbalance of the native oral microbiota, being considered a serious public health problem. The aim of this study was to investigate the association between socioeconomic, pre-, peri- and post-natal factors and ECC in a Brazilian population. This cross-sectional study included 44 women and 44 children, recruited at the Baby Clinic at Universidade Positivo. Only mothers who agreed to sign the informed consent form were included. Children and mothers who reported any type of chronic disease and syndromes, or who reported using any type of continuous medication at the time of data collection were excluded. Socioeconomic data were collected, as well as information from the pre-, peri- and post-natal periods. The data referring to the prenatal period comprised the gestational age on the first prenatal consultation with an obstetrician, the use of folic acid, the use of vitamins and whether the pregnancy was risky or not. The data referring to the perinatal period included the type of delivery, complications during delivery, duration of labor, birth weight, prematurity and APGAR in the first and fifth minutes. Child-related factors included brushing habits, use of fluoride toothpaste, breastfeeding, history of allergies, history of non-chronic respiratory infections and history of hospitalization. In addition, maternal anxiety was assessed using the Trait Anxiety Inventory (STAI). The mothers and children were submitted to clinical examination. Data regarding the index of decayed, missing and filled permanent teeth (DMFT) and the index of decayed, missing and filled primary teeth (dmft) were recorded. To assess the normality of the data, the Shapiro-Wilk test was used. To compare the means between the dmft and the other variables, the Mann-Whitney and Kruskall-Wallis tests with Dun were used. Linear regression analyzes were performed, as well as Spearman's correlation. The data were analyzed using the software IBM SPSS Statistics 23.0 and GraphPad Prism 8.0.0. The level of significance adopted was 5%. The mean age of women was 28.2 years (SD = 6.5), and 70.6% of them completed high school. The children's mean age was 32.1 months (SD = 10.5), 45.5% of the children were girls and 54.5% were boys. Among them, 68.2% were diagnosed with ECC. Among them, 22.7% had low caries activity, 27.3% had medium caries activity and 18.2% had high caries activity. None of the prenatal and perinatal factors assessed were associated with ECC. Family income of up to two minimum wages was found in 70.5% of cases. Family income and and self-perceived maternal depression was associated with ECC (p = 0.035 and p = 0.05, respectively). DMFT was associated with ECC (R = 0.29; CI = -0.015 to 0.547; p = 0.027), as well as the children's average age (R = 0.28; CI = -0.017 to 0.545; p = 0.028). The use of artificial feeding was associated with ECC (p = 0.015). Considering the information obtained, this study provides evidence that ECC can be influenced by socioeconomic, maternal, and child-related factors.